Determination of the Optimum Gamma Ray Lethal Dosage for Mutation Breeding of Indonesian Cassava Genotype Mentega 2 - Fitriani, Hani; Fathoni, Ahmad; Hartati, N Sri; Sudarmonowati, Enny (Jurnal Ilmiah Aplikasi Isotop dan Radiasi, 2021)
This study aimed to determine the optimum lethal dosage (LD50) of gamma rays in cassava and to study the effect of gamma irradiation on the morphological characters. Gamma rays is one of the physical mutagens that has been widely used for mutation breeding to improve the genetic traits of several crops including cassava. A total of 72 plantlets of Indonesian cassava genotype (Mentega 2) were cultured on Murashige & Skoog (MS) medium containing 2% of sucrose and were exposed to 0, 5, 15, 30, 50, and 75 Gray (Gy) using a Cobalt-60 source at dose rate of 600 Gy/h. Morphological characters such as plant height, leaf number, leaf width and length, and root number and length were measured. The percentage of plant survival decreased with the increase of gamma rays dose. The lowest survival rate (17%) was shown by 75 Gy-treated samples. The morphological characters’ observation at 60 days of treatment showed the highest plant height was obtained from 15 Gy-treated samples (12.41±1.84 cm), while the lowest plant was from 75 Gy-treated samples (2.08±1.98 cm) compared to control (4.17+1.46 cm). The LD50 value was calculated to be 29.7 Gy which will be referred for further studies.